(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This article highlights the role of parasitology in human biology and chemistry, its impact on health, and precautionary measures. Parasitology is an important scientific field that studies parasites living in the human body, their development, and their biological and medical properties. Worldwide, there are over 300,000 known parasite species, with each human on average hosting three types of parasites. In biology, parasitology helps to understand the mechanisms of parasite effects on human cells and organs. In chemistry, it studies metabolic processes, toxins, and biologically active substances related to parasites, which is crucial for developing new medications. Furthermore, parasitology plays a vital role in maintaining human health, preventing and treating diseases, and emphasizes the importance of personal hygiene and safety measures.